Mitochondria: Potential Targets for Osteoarthritis - Mao, Xingjia; Fu, Panfeng; Wang, Linlin; Xiang, Chuan (Frontiers in Medicine, 2020)
Osteoarthritis (OA) is a common and disabling joint disorder that is mainly characterized by cartilage degeneration and narrow joint spaces. The role of mitochondrial dysfunction in promoting the development of OA has gained much attention. Targeting endogenous molecules to improve mitochondrial function is a potential treatment for OA. Moreover, research on exogenous drugs to improve mitochondrial function in OA based on endogenous molecular targets has been accomplished. In addition, stem cells and exosomes have been deeply researched in the context of cartilage regeneration, and these factors both reverse mitochondrial dysfunctions. Thus, we hypothesize that biomedical approaches will be applied to the treatment of OA. Furthermore, we summarized the global status of mitochondria and osteoarthritis research in the past two decades, which will contribute to the research field and the development of novel treatment strategies for OA.